Interception of fertile soil phosphorus leaching with immobilization materials: Recent progresses, opportunities and challenges. (December 2022) - Peng, Yutao; Zhang, Tiantian; Tang, Bingbing; Li, Xiaoyun; Cui, Shihao; Guan, Chung-Yu; Zhang, Baige; Chen, Qing
Abstract: The non-point source pollution induced by phosphorus (P) leaching from fertile soils is accelerating the eutrophication phenomena in aqueous ecosystems. Herein, to alleviate and intercept the P leaching from the fertile soils, diverse P immobilization materials (PIM) which can transform labile P into stable P via a range of physicochemical and biological interactions have been adopted and received increasing research interest. However, the remediation mechanisms of different PIMs were complex and vary with soil properties and PIM application methods. In this review, the P fraction and mobility characteristics of different fertile soils were first introduced. Then, three kinds of PIM including inorganic materials ( e.g ., clay minerals and red mud), organic materials ( e.g ., polyacrylamide), and composites ( e.g ., modified biochar) applied in soil P leaching interception were concluded. The key factors ( i.e., soil pH, soil texture, organic matter content and variable soil moisture) influencing PIM performance and potential PIMs used for reducing soil P leaching were also introduced. Current review can favor for proposing more suitable and insightful strategies to regulate the fertile soil P and achieve the dual goals of improving the crop land quality and yield, and preventing agricultural non-point source pollution. Graphical abstract: Image 1 Highlights: Phosphorus fractions and mobility of typical fertile soils were introduced. Fertile soil phosphorus thresholds ranges from 12.5 to 80.0 mg kg −1 Carbon-based and Ca/Al/Fe-based materials were commonly used in reducing fertile soil P loss. Novel carbon and transition elements like cerium and lanthanum modified materials show good potentials. Key factors include soil pH, texture, organic matter content and variable soil moisture.